Evaluating the Impact of Eosinophil Count on the Long-term Clinical Outcomes of Patients With an Acute ST-segment Elevation Myocardial Infarction Who Require Emergency Percutaneous Coronary Intervention: Results of a Multicenter Cohort Study - Lei Guo; Hao Liu; Zhichao Dong; Xuchen Zhou; Hao Zhu; Xia Gu; Bo Zhang; Hanjia Gao; Xiaoxia Fu (Cardiology Discovery)
Abstract. Objective:. Eosinophils (EOS) are inflammatory innate immune cells that play an important role in arterial thrombogenesis. There is a paucity of data on whether EOS levels have an impact on long-term outcomes following ST-segment elevation myocardial infarction (STEMI). This study aimed to investigate the impact of EOS count on the clinical outcomes of STEMI patients who underwent emergency percutaneous coronary intervention (PCI). Methods:. This is a retrospective multicenter cohort study. A total of 754 patients with STEMI who required emergency PCI at 5 centers were screened between October 2015 and November 2016. Patients were divided into 2 groups based on EOS count: EOS count <0.02 × 109/L group (n = 264) and EOS count ≥0.02 × 109/L group (n = 490). Baseline demographic characteristics, clinical information, and medical test data were collected at study entry. The primary endpoint was all-cause death. The secondary endpoint was a major adverse cardiac event. Multivariablete Cox regression analysis was performed to identify the independent predictors of all-cause death, with a follow-up period of 5 years. Results:. The incidence of all-cause death (14.8% vs. 7.6%, P = 0.002) and major adverse cardiac event (20.1% vs. 13.1%, P = 0.011) were significantly higher in EOS count <0.02 × 109/L group compared with ≥0.02 × 109/L group. Multivariablete Cox regression analysis showed that an EOS count <0.02 × 109/L, age ≥65 years, previous heart failure, previous stroke, and left ventricular ejection fraction ≤ 40% were independent predictors of all-cause death in patients with STEMI who underwent an emergency PCI. Conclusions:. Low EOS counts were associated with all-cause mortality in STEMI patients who underwent emergency PCI.